O PROCEDIMENTO DE EMBARGOS POR BENFEITORIAS E O CÓDIGO DE PROCESSO CIVIL - Bacelar Junior, Anselmo Luiz (2022)
This work proposes a study of embargoes per improvements, seeking a systematization of the procedural implements of the right of retention, also analyzing the forms of defense applicable in the process, as well as the subsequent steps to embargoes per improvements, such as anticipated injunctions and appeals in the execution that deal with the right of retention. To this end, it uses the analysis of national and foreign legal literature for the systematization of embargoes per improvements in the 2015 Civil Procedure Code, proposing a study of possession, the right of retention to, finally, properly analyze the element procedure of embargoes of retention for improvements. With this study, we propose a review of art. 538 of the Code of Civil Procedure, in a study of judgments by the Superior Court of Justice on the subject, on the appropriate time for the presentation of the defense on the right of retention in the knowledge process. As a rule, this defense takes place in the impugnment, however, with the study of embargoes of retention for improvements, it is verified the possibility of importing techniques of the executive process to comply with the sentence, studying, together with this perspective, the existing preclusions in the defense of merit in the process, specifically with regard to the right of retention. Thus, it is intended to contribute to a procedural systematization of the right of retention in embargoes per improvements, launching the debate on the importation of techniques of execution for the execution of judgment in the theme of the appropriate moment of the presentation of the right of retention and the discussion on the occurrence of the estoppel in the event of failure to present this defense in the impugnment. With this, the studies on the subject are updated and the procedural discussions are expanded both in the field of execution, extending the debate on the procedural aspects of the right of retention in the 2015 Civil Procedure Code.